Digestive enzymatic responses of chickens feed-restricted and refed as affected by age - Duarte, Cristiane R. A.; Vicentini-Paulino, Maria L. M. [UNESP]; Pinheiro, Daniela F. [UNESP] (Japan Poultry Science Assoc, 2014)
The effect of feed restriction and refeeding on enzymatic activity and gastrointestinal organ weight was evaluated in chickens at two ages, 7 and 35 d of age. At each age, the birds were 70% feed-restricted for 7 d (30% of ad libitum intake) followed by ad libitum refeeding for 3 d. The control groups were fed ad libitum during equivalent periods (10 d). Pancreatic activity of chymotrypsin, trypsin, amylase and lipase, and intestinal activity of sucrase and maltase were analyzed, and the weights of the proventriculus, gizzard, pancreas, small and large intestine were obtained. Trypsin and amylase activity were lower in the feed-restricted group than in the control groups at d14, whereas sucrase activity was lower in the feed-restricted group than in the control group at d42, showing that the effect of feed restriction on enzyme activity was age-dependent. Feed restriction decreased the weight of all organs in the starter and finisher periods. Upon refeeding, the organ weight increased and reached that of the control group only in chickens that were feed-restricted from d35 to d42. In the starter period, proventriculus and gizzard were less affected by feed restriction. In the finisher period, the gizzard was also the least affected organ, while the small intestine was the most affected. All effects of feed restriction were reversed after 3 days of ad libitum refeeding, indicating that the alterations were fast and reversible. Moreover, response to feed restriction and refeeding is age dependent.
Keywords: digestive enzymes; feed restriction; gastrointestinal organs; refeeding